2016
DOI: 10.21037/jtd.2016.12.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gender on perioperative outcomes after robotic-assisted pulmonary lobectomy

Abstract: Background: Female gender has been associated with worse outcomes after cardiovascular surgery and critical illness. We investigated the effect of gender on perioperative outcomes following robotic-assisted pulmonary lobectomy. 44.5%; P=0.004), the most common of which, in both women and men, were prolonged air leak for ≥7 days (13.0% vs. 22.7%, P=0.03), atrial fibrillation (7.1% vs. 14.8%, P=0.04), and pneumonia (7.8% vs. 10.2%, P=0.49). Hospital length of stay (LOS) (4±0.3 vs. 5±0.5 days) was also shorter fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…16 In addition, robotic-assisted pulmonary lobectomy was shown to produce similar rates of intraoperative complications in both sexes but fewer postoperative complications in women. 17 Consistent with previous literature, we found that squamous cell carcinoma histology and high-grade tumor were the factors associated with significantly worse OS. Squamous cell carcinoma histology is an independent prognosticator of worse survival in patients with early-stage NSCLC, 18 and patients with stage I squamous cell carcinoma have significantly worse outcomes than patients with stage I adenocarcinoma.…”
Section: Discussionsupporting
confidence: 92%
“…16 In addition, robotic-assisted pulmonary lobectomy was shown to produce similar rates of intraoperative complications in both sexes but fewer postoperative complications in women. 17 Consistent with previous literature, we found that squamous cell carcinoma histology and high-grade tumor were the factors associated with significantly worse OS. Squamous cell carcinoma histology is an independent prognosticator of worse survival in patients with early-stage NSCLC, 18 and patients with stage I squamous cell carcinoma have significantly worse outcomes than patients with stage I adenocarcinoma.…”
Section: Discussionsupporting
confidence: 92%
“…Female gender has been linked to shorter length of stay and fewer postoperative complications. 39,40 We found no difference in pain between the groups 3 months after surgery. This is in contrast to the results presented by Reeve et al 15 This could be due to the fact that the patients in our study reported low levels of pain, with 50% of the patients reporting no pain at rest.…”
Section: Discussionmentioning
confidence: 53%
“…Female gender has been linked to shorter length of stay and fewer postoperative complications. 39,40…”
Section: Discussionmentioning
confidence: 99%
“…Explanations for these findings are still elusive; however, these findings suggest that sex may modify the impact of other factors on mortality. Other centers have similarly shown that perioperative complications are decreased among women after lung resection [16][17][18][19][20][21]. In terms of unplanned readmission after lung resection, results are mixed, with some studies showing no relationship by sex [37,38], and other large database studies showing an increased risk among men of unplanned readmission [21,39,40].…”
Section: Commentmentioning
confidence: 99%
“…Prior studies have shown that the risk of perioperative complications between men and women after lung resection are different [15][16][17][18][19][20][21]. However, limitations of these prior studies include unmeasured confounding, lack of important granular detail from nationwide databases, and mixed results.…”
mentioning
confidence: 99%